Cultura associada de feijão e milho: III - Efeitos de populações de plantas sobre o feijão da «seca» - Aidar, Homero; Vieira, Clibas (Revista Ceres, 2025)
Two experiments were carried out at Vicosa, state of Minas Gerais, Brazil, in which maize was planted at the beginning of the rainy season and field bean (Phaseolus vulgaris L.) was sowed between the maize rows, when the maize had begun to dry.